Acts of faith - Segal, Erich (New York : Bantam Books, 1993)
They met as children, innocents from two different worlds. And from that moment their lives were fated to be forever entwined. Timothy : Abandoned at birth, he finds a home--and a dazzling career--within the Catholic Church. But the vows he takes cannot protect him from one soul-igniting passion. Daniel : The scholarly son of a great rabbi, he is destined to follow in his father's footsteps. And destined to break his father's heart. Deborah : She was raised to be docile and dutiful--the perfect rabbi's wife--but love will lead her to rebellion. And into world's the patriarch would never dare imagine. Reaching across more than a quarter of a century, from the tough streets of Brooklyn to ultramodern Brasilia to an Israeli kibbutz, and radiating the splendor of two holy cities, Rome and Jerusalem, here is Erich Segal's most provocative and ambitious novel to date--the unforgettable story of three extraordinary lives...and one forbidden love.
Keywords: Faith -- Fiction; Love stories